The Representation of Encounter and Destiny in the Lyrics of “HELLO” by ZEROBASEONE (A Ferdinand de Saussure Semiotic Analysis) - Yoseph Satria Praka; Vellisya Afifa Qonita; Alya Azzahra (Program Studi Pendidikan Musik, 2026)
K-Pop songs function not only as entertainment but also as a medium for conveying emotional messages and representing meanings closely related to listeners’ experiences. The song “HELLO” by ZEROBASEONE is a ballad that represents feelings of encounter, emotional attachment, and belief in destiny, particularly within the context of a group formed through a survival program and bound by a limited activity period. This study aims to analyze the representation of encounter and destiny in the lyrics of “HELLO” using Ferdinand de Saussure’s semiotic approach. The research employs a qualitative descriptive method, with data collected through lyric documentation and analyzed using the concepts of signifier and signified. The results reveal that the lyrics of “HELLO” construct the meaning of encounter as an emotionally charged moment filled with anticipation, which gradually develops into awareness of mutual attachment and culminates in the belief that the relationship is part of an inevitable destiny. The word “hello” is represented not merely as a greeting, but as a symbol of beginnings, continuity, and resistance to separation. In conclusion, this study demonstrates that “HELLO” represents encounter and destiny as emotional meaning constructions shaped by language, experience, and social context, reinforcing the role of music as a medium for expressing collective emotions between ZEROBASEONE and their fans.